Transcriptomic responses of a simplified soil microcosm to a plant pathogen and its biocontrol agent reveal a complex reaction to harsh habitat - Perazzolli, Michele; Herrero, Noemí; Sterck, Lieven; Lenzi, Luisa; Pellegrini, Alberto; Puopolo, Gerardo; Van de Peer, Yves; Pertot, Ilaria (BMC genomics, 2016)
BACKGROUND: Soil microorganisms are key determinants of soil fertility and plant health. Soil phytopathogenic fungi are one of the most important causes of crop losses worldwide. Microbial biocontrol agents have been extensively studied as alternatives for controlling phytopathogenic soil microorganisms, but molecular interactions between them have mainly been characterised in dual cultures, without taking into account the soil microbial community. We used an RNA sequencing approach to elucidate the molecular interplay of a soil microbial community in response to a plant pathogen and its biocontrol agent, in order to examine the molecular patterns activated by the microorganisms. RESULTS: A simplified soil microcosm containing 11 soil microorganisms was incubated with a plant root pathogen (Armillaria mellea) and its biocontrol agent (Trichoderma atroviride) for 24 h under controlled conditions. More than 46 million paired-end reads were obtained for each replicate and 28,309 differentially expressed genes were identified in total. Pathway analysis revealed complex adaptations of soil microorganisms to the harsh conditions of the soil matrix and to reciprocal microbial competition/cooperation relationships. Both the phytopathogen and its biocontrol agent were specifically recognised by the simplified soil microcosm: defence reaction mechanisms and neutral adaptation processes were activated in response to competitive (T. atroviride) or non-competitive (A. mellea) microorganisms, respectively. Moreover, activation of resistance mechanisms dominated in the simplified soil microcosm in the presence of both A. mellea and T. atroviride. Biocontrol processes of T. atroviride were already activated during incubation in the simplified soil microcosm, possibly to occupy niches in a competitive ecosystem, and they were not further enhanced by the introduction of A. mellea. CONCLUSIONS: This work represents an additional step towards understanding molecular interactions between plant pathogens and biocontrol agents within a soil ecosystem. Global transcriptional analysis of the simplified soil microcosm revealed complex metabolic adaptation in the soil environment and specific responses to antagonistic or neutral intruders.
Keywords: metagenom; Gene expression; High-Throughput Nucleotide Sequencing; shluková analýza; Microbial interaction; metagenomika; stanovení celkové genové exprese; Metagenome; půdní mikrobiologie; Computational Biology; Metagenomics; Plant Roots; Biological control; anotace sekvence; Plant pathogen; vysoce účinné nukleotidové sekvenování; Soil Microbiology; interakce hostitele a patogenu; Soil microbial community; Molecular Sequence Annotation; exprese genu; ekosystém; Transcriptomics; Ecosystem; transkriptom; Host-Pathogen Interactions; RNA-Seq; Transcriptome; Cluster Analysis; kořeny rostlin; výpočetní biologie; Gene Expression Profiling; Gene Expression; Soil transcriptome